Assessment of Maximal Oxygen Consumption and Resting Heart Rate among Type 2 Diabetes Mellitus Males during a 12 Week Exercise Program - Rakesh H. Tomar,; Mohammed H. Hashim,; Mohammad H. Al-Qahtani, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The objective of the present study is to investigate the effects of aerobic training on maximal oxygen consumption, resting heart rate, body mass index and body weight in males with conducted on type 2 diabetes mellitus. Twelve week closely supervised aerobic training program was twelve inactive men with type 2 diabetes mellitus (age 25 - 55 yrs.). Two patients discontinued training for different reasons. Intensity of training was from 40-60% of maximum heart rate, duration 30-40 minutes, and frequency 3 times a week. Results showed a significant difference in pre and post means of maximal oxygen consumption and resting heart rate. Mean maximal oxygen consumption improved from 59.66 ± 4.73 to 68.88 ± 4.73 ml/kg/min [t (9) = -3.03, P < 0.016]. Improvement were also seen in mean resting heart rate from 82.28 ± 9.14 to 74.42 ± 6.82 beats/minute [t (9) = 2.89, P < 0.027]. No significant improvement was seen in body mass index [t (9) = 1.17, p > 0.285] and body weight [t (9) = 1.09, p > 0.317]. Twelve week aerobic training was effective in improving maximal oxygen consumption and resting heart rate in male diabetic patients. However, training was not effective enough to reduce body weight and body mass index in diabetic patients.